The Influence of School Principal Leadership, Motivation, and Interpersonal Communication on Teacher Performance - Sumiati La Huni; Novalien C. Lewaherilla; Conchita V. Latupapua (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study explores the influence of principal leadership, work motivation, and interpersonal communication on teacher performance in elementary schools in the Teluk Ambon District, Ambon City. The results reveal that each of these factors significantly impacts teacher performance, with principal leadership emerging as the most influential contributor. Furthermore, the study confirms that the combined effect of these variables plays a vital role in enhancing teacher outcomes. Effective school leadership improves resource management, fosters a supportive work environment, and strengthens teacher professionalism. Work motivation sustains teacher engagement and commitment, while strong interpersonal communication promotes collaboration and reduces conflict. These findings are consistent with previous research and offer practical implications for advancing school leadership practices and enhancing teacher performance through a strategic emphasis on motivation and communication.